Geochemical and petrographical characteristics of the Madzaringwe formation coal, mudrocks and sandstones in the Vele Colliery, Limpopo Province, South Africa : implications for tectonic setting, provenance and paleoweathering - Denge, Elelwani; Baiyegunhi, Christopher (MDPI, 2021)
The sedimentary rocks of the Madzaringwe Formation in the Tuli Basin have been investigated using geochemical and petrographic methods to reveal their source area composition, tectonic setting, provenance and paleoweathering conditions. The petrographic studies show that the rocks consist mostly of clay minerals and quartz. The major elements geochemistry indicates that the rocks of the Madzaringwe Formation have the same source area. Based on the discriminant function plots, it can be inferred that the rocks are of quartzose sedimentary provenance, suggesting that they were derived from a cratonic interior or recycled orogen. The binary plots of TiO2 versus Zr and La/Sr against Th/Co shows that the rocks were derived from silicic or felsic igneous rocks. The tectonic setting discrimination diagrams of SiO2 against Log (K2O/Na2O), Th–Sc–Zr/10, and TiO2 versus (Fe2O3 + MgO) support passive-active continental margin settings of the provenance. The A–CN–K (Al2O3–CaO + Na2O–K2O) ternary diagram and binary plot of the index of compositional variability (ICV) against chemical index of alteration (CIA) shows that the rocks have been subjected to moderate to intensive weathering. Geochemical and petrographic characteristics of the rocks point to uplifted basement source areas predominantly composed of sedimentary rocks and/or granite-gneiss rocks. These source areas might have been from adjacent areas near the Tuli coalfield which include the Limpopo Belt (igneous and sedimentary rocks), and basement uplifted rocks of the Beit-Bridge Complex, consisting of the granite, granite-gneisses and schists.
Journal article published in the journal of Applied Sciences
Keywords: Geochemistry; Petrography; Madzaringwe Formation; Tuli Coalfield; South Africa; Geochemistry; Petrology; Sedimentary rocks